Ketamine Improves Sepsis-induced Immunosuppression by Attenuating Intracellular Calcium Elevation in Rat Peripheral Mononuclear Cells - Puspita Abidatul Qodariyah; Afiyf Kaysa Waafi; Christian Julio Suhardi; Karina Survival Rofiq; Aswoco Andyk Asmoro; Edi Widjajanto (Research Journal of Life Science, 2018)
Immune response in sepsis divided into two phases, hyper-inflammation (cytokine storm) and hypo-inflammation (immunosuppression). The mechanism of immunosuppression appears to involve apoptosis of immune cells, particularly mononuclear cells and it predisposes to secondary infection that is believed as the predominant driving force for mortality. We aimed to determine the effect of ketamine  on mononuclear cells count related to intracellular calcium contained within these cells during the immunosuppression phase of sepsis.This in vivo study was performed in Rattus Novergicus with Fecal Induced Perionitis (FIP) procedure to induce polymicrobial sepsis. Rats were treated with each respective dose of ketamine (2.5, 5, and 10 mg/kg) 1 hour after sepsis induction. Murine Sepsis Score was measured at 1 and 24 hours post-FIP. After 24 hours, animals were sacrificed, and the percentage of intracellular calcium inside CD4, and CD8 T cells, B cells and monocytes, along with these cells counts were determined with flowcytometry.  There are significant elevation of intracellular calcium in CD4 T-cells, B-cells and monocytes after FIP-induction and ketamine treatment suppressed this FIP-induced elevation. Measurement of mononuclear cells count showed a relevant result, in which FIP induced mononuclear cells massive loss and ketamine could inhibit the loss. MSS data showed ketamine 5 mg/kg could improve 24 hours MSS with 100% survivability.These findings suggest that ketamine have an inhibitory effect in mononuclear-cells apoptosis mechanism through attenuating intracellular calcium elevation in polymicrobial sepsis. These inhibitory effects of ketamine might correlate with a better survival and clinical outcome.